2012
DOI: 10.1111/j.1525-1314.2012.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of deformation and metamorphism during subduction and exhumation of hydrated oceanic mantle: Insights from the Western Alps

Abstract: Petrological investigations supported by multi-scale structural analysis of eclogitized serpentinite in the Zermatt-Saas Zone of the Western Alps allows for the determination of mineral assemblages related to successive fabrics, upon which the P-T-d-t path of these hydrated mantle rocks can be inferred. Serpentinites of the upper Valtournanche, with lenses and dykes of metagabbro and meta-rodingite, display an Alpine polyphase metamorphic evolution from eclogite to epidote-amphibolite facies conditions associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 48 publications
(84 reference statements)
10
81
0
Order By: Relevance
“…Thus, the serpentinites represent hydrated mantle peridotites probably from the subducted lithosphere and not from the overriding mantle wedge. Similarly to other sectors of the ZSZ (e.g., Li et al, 2004;Rebay et al, 2012;Zanoni et al, 2011) the schistosity observed in the ZSZ serpentinites at Trockener Steg location may be ascribed to the eclogitic S 2 fabric, where metamorphic olivine is distributed along the pervasive foliation plane (Fig. 4d & e).…”
Section: Field Aspects and Rock Associationsmentioning
confidence: 93%
See 3 more Smart Citations
“…Thus, the serpentinites represent hydrated mantle peridotites probably from the subducted lithosphere and not from the overriding mantle wedge. Similarly to other sectors of the ZSZ (e.g., Li et al, 2004;Rebay et al, 2012;Zanoni et al, 2011) the schistosity observed in the ZSZ serpentinites at Trockener Steg location may be ascribed to the eclogitic S 2 fabric, where metamorphic olivine is distributed along the pervasive foliation plane (Fig. 4d & e).…”
Section: Field Aspects and Rock Associationsmentioning
confidence: 93%
“…However, variations in the rate of subduction have been reported from the Piemonte-Liguria oceanic slab, which result from an interplay between density, geometry of the slab and mantle viscosity (Groppo et al, 2009;Peacock and Wang, 1999;Royden and Husson, 2006). The ZSZ rocks preserve different deformation stages, in which one or more eclogite facies foliations related to Alpine subduction (S 1 and S 2 ) are overprinted by a late stage greenschist facies foliation (S 3 ) (Pleuger et al, 2007;Rebay et al, 2012;Zanoni et al, 2012).…”
Section: Geological Frameworkmentioning
confidence: 97%
See 2 more Smart Citations
“…It is thought to derive from the distal portion of the Adriatic passive margin that was involved in the Alpine subduction (Dal Piaz, 1999;Beltrando et al, 2014). The Sesia Zone is bounded to the west by blueschist to eclogite facies subunits derived from the Piemonte-Liguria Ocean (Bearth, 1967;Dal Piaz and Ernst, 1978;Martin et al, 1994;Cartwright and Barnicoat, 2002;Bucher et al, 2005;Groppo et al, 2009;Rebay et al, 2012;Negro et al, 2013) and to the east by the Insubric Line. This dextral brittle fault separates the Sesia Zone from the southern Alps, which show a weak Alpine imprint at sub-greenschist facies (Bertolani, 1959;Zingg, 1983).…”
Section: Geological Setting and Previous Work On Garnetmentioning
confidence: 99%